Two-point Compression POCUS sebagai Metode Diagnosis Dini Trombosis Vena Dalam Proksimal - Ramadan, Edwin Ti; Maharani, Sausan Hana; Cahyanur, Rahmat; Priantono, Dimas; Rajabto, Wulyo (Jurnal Penyakit Dalam Indonesia, 2024)
Deep vein thrombosis (DVT), especially in the proximal part of the lower extremity, might progress to pulmonary embolism and be fatal. Therefore, it is crucial to prompt the diagnosis of DVT in the emergency room (ER). Due to its efficiency and patient convenience, duplex ultrasound has become the preferred diagnostic method for DVT. Point-of-care ultrasonography (POCUS) was known as a simpler and faster way to use ultrasonography at the bedside. The two-point compression method has become frequently used due to its ability to take less time for examination, yet there are still concerns about its accuracy. This study was conducted to find out whether two-point compression POCUS can be used as an early diagnostic method for proximal DVT. The literature search was carried out in the databases PUBMED, EMBASE, and SCOPUS on March 29, 2023, using keywords “Deep Vein Thrombosis”, “two-point compression POCUS”, and “diagnosis”. Four publications were chosen from the search results. One cross-sectional study was found to have a low validity value because POCUS and Doppler ultrasound operators were not blinded, and the reference test was only performed on positive DVT results on POCUS. All studies had high sensitivity and specificity (>90%) compared to the reference test, except for one cross-sectional study in critical patients in ICU, which had a 63% sensitivity value. In conclusion, the two-point compression POCUS method can be utilized as an early diagnostic method for proximal DVT, with the disclaimer that POCUS operators should get curriculum-based training before doing the examination.